PERAN PEOPLE FOR THE ETHICAL TREATMENT OF ANIMALS (PETA) DALAM KASUS ANIMAL TESTING TERHADAP HEWAN LUWAK DI INDONESIA TAHUN 2012-2014 - Ambarrini, Tantin; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
More than 100 million animals every year suffer and die by fierce chemical test, medical, food, and cosmetic by giving poisonous, blinding and killing million animals every year for irresponsible companies. In medical world, all procedures that are done against the animals called animal testing.Animal testing happens in Indonesia against civet cat animal. The animal eats coffee fruit and digests it to be coffee fruit seed that is put out with its feces. This seed that has unique taste and high price so that there is attraction for the coffee producers to produce civet cat’s coffee seed on a large scale.Hence, the problem is coffee producer method by doing animal testing against civet cat where the process can cause civet cat extinction. Therefore, PETA is one of environmental organization that tries to prevent animal testing method by focusing on main attention with the term of four areas.This research uses anilities descriptive method that explains a thing based on analyze and the data is collected and proved the truth. This research also uses deductive method that the conclusion is made general-specifically. The data collecting is literature study by collecting secondary data and it is based on librarian research like book, relevant journal, newspaper, and internet.Keywords: animal testing, civet cat, PETA